Allogeneic Hematopoietic Stem Cell Transplantation for Leukocyte Adhesion Deficiency. Issue 2 (March 2018) - Horikoshi, Yasuo; Umeda, Katsutsugu; Imai, Kohsuke; Yabe, Hiromasa; Sasahara, Yoji; Watanabe, Kenichiro; Ozawa, Yukiyasu; Hashii, Yoshiko; Kurosawa, Hidemitsu; Nonoyama, Shigeaki; Morio, Tomohiro
Abstract : The clinical outcome of allogeneic hematopoietic stem cell transplantation (HSCT) was retrospectively analyzed in 6 patients with leukocyte adhesion deficiency. Of 3 patients transplanted with myeloablative conditioning, 2 patients had complete chimerism and 1 patient had mixed chimerism. By contrast, all 3 patients transplanted with reduced-intensity conditioning (RIC) had mixed chimerism, one of whom progressed to secondary graft failure. All patients with low-level mixed chimerism and secondary graft failure were rescued by donor lymphocyte infusion or a second HSCT. RIC-HSCT is feasible for leukocyte adhesion deficiency, although further refinement/modification of conditioning is required to achieve higher donor chimerism levels.